(untitled) (Research, Society and Development, 2021)
Digital Information and Communication Technologies (TDIC) have significantly influenced the way in which the school has built its pedagogical practices. Especially in this scenario, the Curriculum Component called “Physical Education” was able to reorganize and foster new ways of working with bodily practices in the educational context. This work describes the contributions of a proposal in which technology is thought of as a didactic device in schools, with the aim of proposing reflections on the different possibilities that the (TIDC) offer for Physical Education (PE) classes in high school. It was a case study, in which 35 Students of a Licentiate Course in PE built and analyzed didactic sequences permeated by different ways of using educational technologies based on instructional and constructionist approaches to information technology in education. The study clarifies that instructional methods in PE reinforce the technicist, mechanistic and technical character of human movement, while constructionist methods are directed towards classes with active and more significant methodologies. In this second approach, the teacher gains the status of mediator of knowledge, opening the possibility for the construction of more autonomous and collaborative pedagogical practices. Finally, it clarifies that the 06 (six) thematic units presented by the Common National Curriculum Base (in Portuguese, BNCC) may benefit from more critical and multiculturalist pedagogical perspectives in the context of PE in schools.